Model of Internalization Religious Character Values to Strengthen Moral Student - Nursalim, Eko; Zurqoni, Zurqoni; Khojir, Khojir (TARBIYA: Journal of Education in Muslim Society, 2023)
AbstractThis study aimed to investigate the implementation of religious character values among students and to identify internalisation models that can enhance students’ morale. Employing qualitative methods, the study adopted a phenomenological approach to comprehensively understand the process of internalising religious character values in an educational setting. This study was conducted across two senior high schools and one vocational high school in East Kalimantan Province. Moreover, data were gathered through extensive interviews, observations, and documentation, then analysed through data reduction, data display, and conclusion drawing. The findings revealed various efforts to instil students' religious character values, such as instilling theoretical knowledge about spiritual values, organising religious activities, fostering a religious culture in schools, integrating religious values in various disciplines, and maintaining continuous supervision. The model utilised for internalising religious character values was the structural-organic-reflective-integrative model. This model offers a comprehensive approach to enhancing students' moral development by embedding religious principles into every aspect of education. While this study has contributed to the discussion, some limitations and suggestions for future research were provided.AbstrakPenelitian ini bertujuan untuk menginvestigasi implementasi nilai-nilai karakter religius di kalangan siswa dan mengidentifikasi model internalisasi yang dapat meningkatkan moral siswa. Dengan menggunakan metode kualitatif, studi ini mengadopsi pendekatan fenomenologis untuk memahami secara komprehensif proses internalisasi nilai-nilai karakter religius dalam konteks pendidikan. Penelitian ini dilakukan di dua sekolah menengah atas dan satu sekolah menengah kejuruan di Provinsi Kalimantan Timur. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi, yang kemudian dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian ini menunjukkan berbagai upaya untuk menanamkan nilai-nilai karakter religius siswa, seperti memberikan pengetahuan teoritis tentang nilai-nilai spiritual, mengorganisir kegiatan keagamaan, membina budaya keagamaan di sekolah, mengintegrasikan nilai-nilai keagamaan dalam berbagai disiplin, dan menjaga pengawasan yang berkelanjutan. Selanjutnya, model internalisasi nilai-nilai karakter religius yang diterapkan adalah model struktural-organik-reflektif-integratif. Model ini menawarkan pendekatan komprehensif untuk meningkatkan perkembangan moral siswa dengan menyelipkan prinsip-prinsip keagamaan ke dalam setiap aspek pendidikan. Meskipun studi ini telah memberikan kontribusi pada diskusi di topik terkait, beberapa keterbatasan dan saran untuk penelitian di masa mendatang telah disampaikan dalam artikel ini.How to Cite: Nursalim, E., Zurqoni, Khojir. (2023). Model of Internalization Religious Character Values to Strengthen Moral Student. TARBIYA: Journal of Education in Muslim Society, 10(2), 163-182. doi:10.15408/tjems.v10i2.37575.